(untitled) (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The purpose of this research is to detect the antibacterial properties of lactic acid bacteria (LAB) against pathogenic bacteria. Materials and Methods: Isolation and determination of Lactobacillus spp. Testing of the antibacterial activity of LAB was conducted using filtrate and nonfiltrate forms. The lactic acid bacterial isolates were confirmed to be identified through Gram staining, cell shape, catalase testing, and motility testing. Results: The results of the analysis of the LAB inhibition zone using filtrate and nonfiltrate forms against the bacteria Bacillus cereus were included in the very strong category. The results of the analysis of the LAB inhibitory zone using filtrate and nonfiltrate forms and the agar well method against Staphylococcus aureus bacteria were classified into the very strong category. The results of the LAB inhibitory zone analysis using filtrate and nonfiltrate forms with the well method against Escherichia coli bacteria are included in the very strong category, whereas the results from the LAB inhibitory zone analysis using the filtrate and nonfiltrate forms with the agar diffusion method (disks) are included in the strong category. Conclusion: Based on the results, LAB isolated from Sumba mare’s milk displayed antibacterial activity in the strong and very strong categories against pathogenic bacteria such as B. cereus, S. aureus, and E. coli. J. Adv. Vet. Anim. Res., 9(1): 53–58, March 2022 http://doi.org/10.5455/javar.2022.i568